Front Cover: Photocatalytic Radical Addition to Levoglucosenone (Eur. J. Org. Chem. 1/2022). Issue 1 (4th January 2022) - Lefebvre, Corentin; Van Gysel, Terence; Michelin, Clément; Rousset, Elodie; Djiré, Djibril; Allais, Florent; Hoffmann, Norbert
Abstract : The Front Cover shows the stereo and regio selective addition of radical species such as alkyl or formamidyl radicals to levoglucosenone. Levoglucosenone is a biobased platform chemical obtained from celluloses. The radical intermediates are generated by hydrogen atom transfer involving photocatalysis with tetra‐ n ‐butylammonium decatungstate (TBADT). Cover picture created with the help of Tony Leclet. More information can be found in the Article by N. Hoffmann et al .